An evaluation of the pharmacy chronic care outreach programme at Zebediela - Ngoepe, Phuti Joel (My University, 2021)
Introduction: Zebediela Hospital in Limpopo Province is running an outreach programme as part of its chronic care initiative. In the programme, pharmacy personnel visit the feeder clinics attached to the hospital to dispense chronic medicines to patients. This study aimed at evaluating how this pharmacy chronic care outreach programme is performing, by looking at pharmacy personnel, nursing personnel and patients’ perceptions. Method: A cross-sectional descriptive study was conducted at the six feeder clinics attached to Zebediela Hospital in the Lepelle-Nkumpi municipality of the Capricorn district in Limpopo Province using a quantitative research method. This quantitative research was administered in the form of a survey. Questionnaires were used to collect data from patients, nursing personnel and pharmacy personnel. A total of 399 participants (n=399) took part in the study. The participants included 337 patients from six different clinics, 18 pharmacy personnel and 44 nursing personnel. Data was analysed using the SPSS version 25.0. Results: The pharmacy personnel showed that an allocation of more than three personnel per duty roster sufficed. Regarding transport used by pharmacy personnel when embarking on the Pharmacy Chronic Care Outreach Programme, 71.4% of pharmacy personnel indicated that they always used hospital transport in 83.3% of the cases. The study findings showed that, 71% of patients agreed they were satisfied with the pharmacy times for collecting medicines apart from the fact that 65.6% of patients travelled for more than two hours from their respective homes to their nearest clinic. Sixty eight percent of pharmacy personnel perceived the PCCOP model to be reducing patient waiting time at the clinics. Both the patients and nursing personnel were however not satisfied with the pharmacy personnel’s arrival time at the clinic. The other negative aspect reported was the space problem at the clinics where, 77.8% of pharmacy personnel and 54.5% of nursing personnel reported this as not user-friendly. The patients’ satisfaction levels regarding the PCCOP model for “very satisfied” stood at 64.2% and 0.6% for “very dissatisfied”. Both pharmacy and nursing personnel recommended that the PCCOP model be continued with recommendations towards improving human resources and infrastructure. Conclusion: In conclusion, both pharmacy personnel and nursing personnel showed that the outreach programme was a good initiative in the health system and it benefitted patients. However, the concerns mentioned by patients included long waiting times at the clinic and medicine stock outs. As the results show, the pharmacy chronic care outreach programme should be continued, as long as patients’ complaints can be attended to. Key words: Evaluation, Pharmacy Chronic care Outreach Programme, Zebediela
Thesis (M. Pharm. (Pharmacology)) -- University of Limpopo, 2021
Keywords: Evaluation; Pharmacy Chronic care Outreach Programme; Zebediela; Chronic diseases - Alternative treatment; Chronically ill; Drug carriers (Pharmacy)